Explorando as affordances do uso de dispositivos móveis na formação continuada de professores da língua inglesa - Ivana Queiroz Pinheiro (2017)
In this study, I pursue a better understanding of how English language teachers use mobile technology devices for their professional development. In order to achieve this objective, I have analyzed the perceptions of the advantages and limitations of using mobile devices in English language teaching and learning. I have identified the emerging affordances of such a use in a virtual environment mediated by the WhatsApp application. Out of those affordances, I have also identified affordances that made it possible to discuss whether the insertion of mobile devices into teacher training programmes can be seen as an innovative action. In the theoretical foundation for this research, I draw attention to the discussions concerning contemporary mobility, technology, teaching and learning (PEGRUM, 20014; SHARPLES et al., 2007; TRAXLER, 2009), as well as the main characteristics and definitions of Mobile Learning, as a relatively new field of study (KUKULSKA-HULME, TRAXLER, 2005; O'MALLEY et al., 2005, CROMPTON, 2013). Next, I describe the uniqueness of the concept of affordance as conceived by Gibsons (1986 [1979]) ecology psychology perspective and by van Liers (2000, 2004) language education area perspective. Being so, I relate this concept to the training of English language teachers, especially in the context of Brazilian education. Finally, I introduce a model of dissemination of innovation based on Rogers (2003). Speaking of its methodology, this research constitutes a case study with qualitative analysis of multimodal data, which were collected from the interaction between teachers during a course of professional teacher development via WhatsApp. This course, called Taba Móvel, integrated two teacher training groups composed by, approximately, 23 participants each. The participating teachers were from several states in Brazil and remained connected for about 8 weeks - the length of the first stage course. The data of this research were collected through written, audio and image recordings of the groups' conversations, participants observation, the application of an online questionnaire at the end of the course and individual interviews held at a distance. The results reveal that the participants perceive the use of mobile technology in teaching as an advantageous idea, particularly because of its motivational aspect. However, they are aware of the challenges and several limitations of such an endeavor. The affordances that have been identified revealed that many of the teachers are already making use of mobile technology for their professional development, for instance, when using smartphone apps to practice their language skills and create chat groups via WhatsApp to discuss the issues of technology and professional development with their colleagues. In addition, the teachers were in agreement with the use of WhatsApp as the communication channel responsible for the dissemination of the idea of using mobile devices in the training of English teachers as an innovative thing.